The Summer Bridge Program: An Effective Agent in College Students’ Retention - Howard, Barbara L.; Sharpe Jr., Lonnie (Journal of Interdisciplinary Studies in Education, 2019)
Student retention is a consequential effort of all institutions of higher learning today.  The survival of the institution is dependent upon the success of students in obtaining their degrees (Knox, 2005; Noel, 1978).  In order to continue to grow a base of Science, Technology, Engineering and Mathematics (STEM) students and produce quality graduates, it is imperative that best practices in student success and retention be identified, documented and replicated.  This study looked at the Tennessee Louis Stokes Alliance for Minority Participation Summer Bridge program results in STEM major retention and success in designated courses.  Three years of the TLSAMP Summer Bridge were randomly chosen from the inception of the first joint TLSAMP Summer Bridge Program in 2004 and the last one in 2013.  The years chosen for this study were 2008, 2012 and 2013.  The following information was gathered for participants in the 2008, 2012, and 2013 TLSAMP Summer Bridge Programs: (1) Major, (2) If student returned to school after freshmen year (3) If a change of major after freshman year, ( (4) First English course grade, and (5) First Math course grade.  TLSAMP Summer Bridge showed an indication to be a best practice for student retention and success in those targeted courses addressed in the bridge program.  From a broader perspective, it can be inferred that what works for STEM majors can also work for other majors when tailored for them and the culture of the institution.  Further study on the effectiveness and implementation of summer bridge programs on student recruitment and student retention is recommended.